The Repercussions of the COVID-19 Pandemic on the Research Production of Faculty Members at Jordanian Universities - Badrakhan, Sawsan S.; Hussein, Jamal Taha; Al Rawashdeh, Omayma; Haimur, Talal Saeed Mohareb (Dirasat: Human and Social Sciences, 2024)
Objectives: The study aimed to reveal the positive and negative repercussions of the COVID-19 pandemic on the research production of faculty members at Jordanian universities. Methods: The study followed the descriptive survey methodology, and data was collected using a validated and reliable questionnaire. It was distributed to a sample of (372) faculty members, who were randomly selected from Jordanian public and private universities. Results: The results showed that the positive effects of the COVID-19 pandemic on research productivity among faculty members in Jordanian universities were generally high, with the most prominent being a shift towards digitizing the university system, libraries, and references. On the other hand, the negative effects of the pandemic on research productivity were moderate, with the most notable being the limited budgets allocated for scientific research in Jordanian universities to address the repercussions of COVID-19. The results also revealed statistically significant differences in the average responses of the study sample individuals towards the scale, attributed to the variable of academic rank, in favor of associate professors, while no differences were found in the rest of the variables. Conclusions: There is a critical need to adopt clear criteria and mechanisms to enhance research collaboration and partnerships between public and private universities to support research output in various fields, taking into account the budget allocated for this purpose.